Airborne and Structure-Borne Noise Control in the MB Truck Cabin Interior by the Noise Reduction in the Transmission Path - MOHAMMADI, Nader (Archives of Acoustics, 2023)
In the current study, investigations are made to control the MB truck cabin interior noise by reducing noise in the transmission path. The main sources of cabin noise include the engine, exhaust system, air inlet system, driveline system, and tyres (especially at higher speeds). Furthermore, vibrations of the body and interior parts of the truck may significantly impact the overall in-cabin sound level. Noise is transmitted into the cabin via air (airborne noise) and cabin structure (structure-borne noise). In the noise treatment phase, noise transmission paths are considered. A viscoelastic layer damping material is used to reduce the vibration amplitude of the cabin back wall. The overall loss factor and vibration amplitude reduction ratio for the structure treated is calculated. Computational results are then compared with the values obtained by the experimental modal analysis results. Choosing the suitable material and thickness can significantly reduce the vibration amplitude. A sound barrier, silicon adhesive, and foam are also utilised for noise control in the transmission path. The effectiveness of the mentioned acoustic materials on cabin noise reduction is evaluated experimentally. The experimental SPL values are reported in the frequency range of 20 Hz–20 kHz based on a 1/3 octave filter. The experimental results show that using acoustics materials reduces the overall in-cabin sound level for a wide range of frequencies.